Ship weather routing optimization with dynamic constraints based on reliable synchronous roll prediction. (15th February 2018) - Krata, Przemyslaw; Szlapczynska, Joanna
Abstract: Ship routing process taking into account weather conditions is a constrained multi-objective optimization problem and it should consider various optimization criteria and constraints. Formulation of a stability-related, dynamic route optimization constraint is presented in this paper. One of the key objectives of a cross ocean sailing is finding a compromise between ship safety and economics of operation. This compromise should be taken into account by the planning procedure and proper optimization algorithm. In this research complex stability-related phenomena are adopted as the basis for the constraint set formulation in weather routing. Thus, the synchronous roll, parametric resonance, surf riding and broaching-to are considered according to the IMO MSC.1/Circ.1228 guidance. However, the dangerous resonance motion of the ship depends on her natural period of roll and a degree of tuning to the encounter wave period. This natural period strictly depends on the GZ curve shape and, consequently, on the amplitude of roll. In order to properly model the natural period of roll, a new method utilizing equivalent metacentric height is applied and incorporated into the route optimization. Sample calculations of the cross ocean routes are presented and the effect of the dynamic approach to the constraint set is demonstrated and discussed. Highlights: Ship resonance roll-related constraints depending on actual amplitude of roll are proposed. Reliable modeling of ship synchronous rolling conditions is applied to weather routing and the equivalent metacentric height is utilized in the optimal route finding process. Significance of equivalent metacentric height application is revealed. Sample route optimization are run and effects of dynamic constraints implementation are presented.